PENGARUH KEPEMIMPINAN, PENGAWASAN DAN SIKAP KERJA TERHADAP KINERJA PEGAWAI DI DINAS PEMBERDAYAAN MASYARAKAT DAN DESA KABUPATEN LABUHANBATU SELATAN - Nurlaili Rambe; Eka Rafika; Muhammad Rahmadani Lubis; Paisal Pahmi Hasibuan; Muhammad Amsal Nasution (Jurnal Prodi Fakultas Ekonomi-UISU, 2021)
The formulation of problem in this research is there is influence leadership on employees performance. There is influence controlling on employees performance. There is work attitude on employees performance. There is influence of leadership, controlling and work attitude on employees performance. The purpose of this research is for know influence and analize of leadership on employees performance. For know influence and analize controlling on employees performance. For know influence and analize work attitude on employees performance. For know influence and analize leadership, controlling and work attitude on employees performance. The sample in this research is 36 employees, with data analysis technique used is multiple linear regression analysis. The research result leadership influence positive and significant on employees performance. controlling influence positive and significant to employees performance. Work attitude influence positive and significant to employees performance. Leadership, controlling and work attitude influence positive and significant to employees performance.